Diagnostic value of C-reactive protein as a predictor of complicated appendicitis like perforated/gangrenous appendicitis - Choudhary, Suresh Kumar; Yadav, Bhanwar Lal; Gupta, Shalu; Kumar, Narender; Bansal, Somendra; Verma, Pradeep Kumar (International Surgery Journal, 2019)
Background: Appendicitis is inflammation of appendix. Appendicitis remains the most common abdominal surgical emergency. There is no reliable specific marker for acute appendicitis and its complications. C- reactive protein is an acute phase reactant produced by the liver during the acute inflammation, which rises rapidly in presence of inflammation. CRP is a more sensitive and reliable indicator of inflammatory processes than ESR and leucocyte count. The aim of this study was to evaluate whether CRP predict the severity of appendicitis. Methods: This study was hospital based, observational study. After history and clinical examination, patient underwent USG whole abdomen. Diagnosis of appendicitis was established. After that patient underwent routine blood investigations including, CRP. After confirming diagnosis of appendicitis, patients underwent appendectomy and biopsy of appendix was sent for histopathological examination. Results: In our study, CRP value > 6.15mg/L has a sensitivity of 100.0% and a specificity of 54% in predicting complicated perforated or gangrenous appendicitis. The positive predictive value and negative predictive value of CRP were 100% and 61.54% respectively. The cut off level at around 6mg/dL needs to be handled carefully and a person with high CRP should undergo surgery immediately. Conclusions: This study clearly suggested that CRP leads to precise prediction of the severity of acute appendicitis for treatment. A person with high CRP should undergo surgery immediately ures.